The Role of Ecotourism in the Social and Economic Field - Muhammad Ali Mustofa (Future Science, 2022)
Ecotourism is an alternative to tourism development that plays a role in the economic field and has a role in the social field through the concept of nature conservation and education. This study aims to analyze the positive impact of the concept of ecotourism in the social and economic fields on the local community. The research method used is field research with a descriptive qualitative approach in Pasar Slumpring, Cempaka Village, Bumijawa District, Tegal Regency. The data was used as primary data in interviews with related groups such as local village heads, heads of tourism awareness groups, ecotourism managers and the local community who participated. The study results show that the application of ecotourism is able to produce a positive impact in the social field, such as encouraging nature conservation, so that it is maintained while providing education on cultural values. Ecotourism also strengthens community social relations through cooperation in implementing and maintaining ecotourism. In addition, ecotourism has a positive impact on the economy, where ecotourism is able to increase the income of the area and the local community through tourist fees and community productivity that act as traders and become a means of absorbing labour to reduce unemployment. Therefore, there is a need for sustainability in maintaining the sustainability of ecotourism, considering that the resulting impact provides benefits for many people.